TEPUNG TALAS VARIETAS BARU SEBAGAI BAHAN BAKU COOKIES KWT SAWARGI KELURAHAN SITU GEDE KECAMATAN BOGOR BARAT - Nurilmala, Febi; Ariesta, Nina; Nurlela, Nurlela; Widhyastini, IGA Manik; Azizah, Mia (Jurnal Abdi Inovatif : Pengabdian kepada Masyarakat, 2022)
The purpose of the following community service activity is to educate KWT Sawargi members through counselling on the use of new varieties of taro plants Febi521 and its post-harvest processing for processed taro production houses, as well as preparing activity plans for implementing the use of new varieties of taro Febi521 and its post-harvest processing. The target group of this activity are the residents of the Women Farmers Group (KWT) Sawargi, Situ Gede Village, West Bogor District, Bogor City. This Community Service activity can be divided into three stages: preparation, implementation, and evaluation. The results of this activity have a positive impact on increasing knowledge and skills and have the potential to improve the economy of the community. KWT members have a new understanding of the new taro variety Febi521, which has the advantage of not itching due to low levels of calcium oxalate. KWT also knows the nutritional value of Febi521 taro. In addition, KWT members also understand Febi521's post-harvest processing techniques and skills in processing taro products in the form of cookies made from taro flour. Sustainability support of this activity, the team provided new varieties of taro seeds Febi521 and production tools for post-harvest processing of taro.Keywords: taro; Febi521, post-harvest, taro flour, cookiesAbstrakKegiatan pengabdian masyarakat bertujuan untuk edukasi kepada mitra KWT Sawargi melalui penyuluhan pemanfaatan tanaman talas varietas baru Febi521 dan pengolahan pascapanennya dan menyusun rencana aktivitas implementasi pemanfaatan tanaman talas varietas baru Febi521. Kegiatan pengabdian kepada masyarakat ini dibagi dalam tiga tahap yaitu, persiapan, pelaksanaan, dan evaluasi. Hasil kegiatan ini memberikan dampak positif terhadap peningkatan pengetahuan, keterampilan, dan berpotensi meningkatkan perekonomian masyarakat Kelurahan Situ Gede, Kecamatan Bogor Barat, Kota Bogor. Anggota KWT memiliki pemahaman yang baru tentang talas varietas baru Febi521 yang memiliki keunggulan tidak gatal karena rendahnya kadar kalsium oksalat. KWT juga memiliki pengetahuan tentang nilai gizi talas Febi521. Selain itu, para anggota KWT juga memahami teknik pengolahan pascapanen talas Febi521 serta memiliki keterampilan dalam mengolah produk olahan talas berupa cookies berbahan dasar tepung talas. Untuk mendukung keberlanjutan kegiatan ini, tim memberikan bibit talas varietas baru Febi521 dan alat produksi olahan talas pascapanen.Kata Kunci: talas, Febi521, pascapanen, tepung talas, cookies